2011
DOI: 10.2215/cjn.08481109
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Abnormal Birth History and Growth in Children with CKD

Abstract: SummaryBackground and objectives Poor linear growth is a well described complication of chronic kidney disease (CKD). This study evaluated whether abnormal birth history defined by low birth weight (LBW; Ͻ2500 g), prematurity (gestational age Ͻ36 weeks), small for gestational age (SGA; birth weight Ͻ10th percentile for gestational age), or intensive care unit (ICU) at birth were risk factors for poor growth outcomes in children with CKD.Design, setting, participants, & measurements Growth outcomes were quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 26 publications
1
42
1
3
Order By: Relevance
“…22 An observational cohort study among 426 children with congenital kidney disease showed that low birth weight and being small for gestational age are risk factors for poor growth outcomes in children with mild and moderate CKD. 23 We observed that younger gestational age and lower gestational age-adjusted birth weight are associated with both a lower kidney volume and a lower eGFR in school-aged children. These findings are in line with previous studies showing that low birth weight for gestational age is associated with kidney function in childhood.…”
Section: Fetal and Early Childhood Growth And Childhood Kidneymentioning
confidence: 60%
“…22 An observational cohort study among 426 children with congenital kidney disease showed that low birth weight and being small for gestational age are risk factors for poor growth outcomes in children with mild and moderate CKD. 23 We observed that younger gestational age and lower gestational age-adjusted birth weight are associated with both a lower kidney volume and a lower eGFR in school-aged children. These findings are in line with previous studies showing that low birth weight for gestational age is associated with kidney function in childhood.…”
Section: Fetal and Early Childhood Growth And Childhood Kidneymentioning
confidence: 60%
“…Whether a more vigorous treatment will translate into better growth outcome in KTx patients needs to be proven in future trials. Intrauterine growth restriction and parental height are significant predictors of total body height in the general population and in children with CKD (27)(28)(29)(30)(31). Malnutrition is an important factor contributing to growth failure in children with CKD, especially during young age.…”
Section: Discussionmentioning
confidence: 99%
“…77 Assessments of the NICU graduate should continue into adolescence, a time when many children see their pediatrician less frequently. Rapid growth in puberty often unmasks renal dysfunction 78 because abnormal kidneys may be unable to accommodate the demands of increased growth.…”
Section: Figurementioning
confidence: 99%